Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1001/jamaophthalmol.2016.3502
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Discrepancy Between Diagnostic Clinical Examination Findings and Corresponding Evaluation of Digital Images in the Telemedicine Approaches to Evaluating Acute-Phase Retinopathy of Prematurity Study

Abstract: IMPORTANCEAs effective treatments for potentially blinding retinopathy of prematurity (ROP) have been introduced, the importance of consistency in findings has increased, especially with the shift toward retinal imaging in infants at risk of ROP.OBJECTIVE To characterize discrepancies in findings of ROP between digital retinal image grading and examination results from the Telemedicine Approaches to Evaluating Acute-Phase Retinopathy of Prematurity study, conducted from May 2011 to October 2013. DESIGN, SETTIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 28 publications
0
34
1
1
Order By: Relevance
“…5,6 The e-ROP study found high sensitivity (90.0%) and specificity (87.0%) for detecting infants who warranted a referral to an ophthalmologist to consider treatment; for example, 1 or both eyes had referral-warranted (RW) ROP, defined as zone I ROP, stage 3 ROP or more, or plus disease. In a recent report, 7 e-ROP investigators presented a review by a consensus panel of ROP experts that examined 161 false-negative and 854 false-positive images from eyes in which findings consistent with RW-ROP were noted either on diagnostic examination or grading, but not both. Based on the panel results, it was estimated that the ROP experts would agree with the clinical examination findings in 46.5% (95% CI, 41.6%–51.6%) of the false-negative cases (ie, RW-ROP found by examination but not by image evaluation) and agree with trained readers’ grading in 70.0% (95% CI, 67.3%–72.8%) of the false-positive cases.…”
mentioning
confidence: 99%
“…5,6 The e-ROP study found high sensitivity (90.0%) and specificity (87.0%) for detecting infants who warranted a referral to an ophthalmologist to consider treatment; for example, 1 or both eyes had referral-warranted (RW) ROP, defined as zone I ROP, stage 3 ROP or more, or plus disease. In a recent report, 7 e-ROP investigators presented a review by a consensus panel of ROP experts that examined 161 false-negative and 854 false-positive images from eyes in which findings consistent with RW-ROP were noted either on diagnostic examination or grading, but not both. Based on the panel results, it was estimated that the ROP experts would agree with the clinical examination findings in 46.5% (95% CI, 41.6%–51.6%) of the false-negative cases (ie, RW-ROP found by examination but not by image evaluation) and agree with trained readers’ grading in 70.0% (95% CI, 67.3%–72.8%) of the false-positive cases.…”
mentioning
confidence: 99%
“…La introducción de la telemedicina en sus diferentes versiones (RetCam, fotos por teléfonos móviles, entre otros) permite el envío de imágenes por redes virtuales que favorecen la consulta en situaciones de duda diagnóstica y/o tratamiento. 13,23,24 Una segunda opinión puede evitar el traslado innecesario de niños de alto riesgo y su consecuente morbilidad agregada.…”
Section: Discussionunclassified
“…allows to send images using virtual networks that facilitate consultation in case of diagnostic suspicion and/or treatment. 13,23,24 A second opinion may prevent the unnecessary transport of high-risk children and the resulting added morbidity.…”
Section: Discussionmentioning
confidence: 99%